Evaluation of Cross-Border Leakages in Community Support Frameworks. The case of Andalusia (Spain). - Antonio Morillas; Laura Moniche; Marc Castro (European Regional Science Association (ERSA), 2004)
The enlargement of the European Union to 25 members implies that relative position of Andalusia will improve with regard to the new GDP per capita average. This fact may derive a reduction in structural funds support for this Spanish region objective 1. This paper is focused in the ex-post assessment of the CSF 1994–99 in Andalusia. Direct and indirect effects, as well as cross-border leakage are analysed. We aim to compare stimuli induced from structural funds in the rest of the national economy with those remaining in Andalusia. If effects on the rest of Spain were important in relative terms, the central idea of regional policy, which defines community convergence tools, would be questioned. Results show evidences for this hypothesis in the case of Andalusia, given the importance of the effects generated in the rest of Spain and the biases of CSF funds towards sectors with a high need for imports, some of which are characterized by an intensive use of the region's natural resources. Key Words: Structural Funds; Ex-post Evaluation; Convergence; Input-Output; Cross-border leakages. JEL classification: C67; C82; R58
Keywords: C67; C82; R58; 330; Structural Funds; Ex-post Evaluation; Convergence; Input-Output; Cross-border leakages